From exhaustive vacation queues to preemptive priority queues with general interarrival times - Fiems, Dieter; De Vuyst, Stijn (Zielona Góra: Uniwersytet Zielonogórski)
We consider the discrete-time G/GI/1 queueing system with multiple exhaustive vacations. By a transform approach, we obtain an expression for the probability generating function of the waiting time of customers in such a system. We then show that the results can be used to assess the performance of G/GI/1 queueing systems with server breakdowns as well as that of the low-priority queue of a preemptive MX+G/GI/1 priority queueing system. By calculating service completion times of low-priority customers, various preemptive breakdown/priority disciplines can be studied, including preemptive resume and preemptive repeat, as well as their combinations. We illustrate our approach with some numerical examples.
Keywords: queueing system; preemptive priority; server interruption; server breakdown; exhaustive vacations